Optical Response Analysis at Various Pb2+ Concentration by Using Fiber Optic Displacement Sensor - Hirman, Nurul Syafiqah; Mohd Taib, Nur Athirah (Malaysian Journal of Science Health & Technology, 2021)
A simple and low-cost Fiber Optic Displacement Sensor (FODS) using reflective intensity modulation technique was developed to analyze various concentrations of Pb2+, a compound classified under heavy metal ions. Lead is harmful to the environment including to human but is used in the cosmetic field for beauty without realizing and considering the hazardousness of lead as it would cause a long-term effect. Therefore, a feasible way has been identified in this study to demonstrate the level of Pb2+ concentration in cosmetics field by employing the theory of modulation of intensity as a function of displacement sensor. The permissible limit according to Malaysian Cosmetics Guidelines and ASEAN Cosmetic Directive was 20 ppm. The concentration sensor’s system exhibits 0.0018 V/ppm sensitivity with a linearity of 96% and 94% respectively, for both peaks. Meanwhile, the sensitivity was 0.034 V/ppm for the first peak and 27.72 V/ppm for the second peak, with slope linearity of more than 96% for surface tension parameter. The credibility of these optical response curves data might be useful, especially in the cosmetic’s industrial application.